Bioremediation Combined with Ozonation Treatment of Polycyclic Aromatic Hydrocarbon Contaminated Soil of an Aged Oil Refinery Using Local Bacteria - Samsami, R.; Marandi, R.; Akhavan Sepahi, A.; Sohrabi, M.R.; Mazhar, F. (Asian Journal of Chemistry, 2010)
The amounts of polycyclic aromatic hydrocarbons (PAHs) were determined in a silty-clay soil sample of an aged oil refinery field in Abadan, Iran. More than 70 aerobic bacteria were isolated from the soil sample. Then 13 of them selected based on ability of growing in liquid mineral media which added anthracene as the sole carbon source. The selected bacteria were used to bioremediation of the same polycyclic aromatic hydrocarbon-contaminated soil in the present of Tween 80. The results show 78.1 % remediation after 30 days incubation at 37 ºC and 180 rpm. Two-phase ozonation and integration of ozonation and bioremediation methods also were studied achieved to 91.1 and 98.4 % in polycyclic aromatic hydrocarbons elimination, respectively. The polycyclic aromatic hydrocarbon contents of all samples were determined instrumentally by high performance liquid chromatography. It was found that the using of local bacteria resulted in a high efficiency bioremediation of soil. The results also demonstrated that removal of 3-ring polycyclic aromatic hydrocarbons is faster than 4-ring and 5-ring polycyclic aromatic hydrocarbons during bioremediation. No significant different seen in polycyclic aromatic hydrocarbon degradation between 3-ring, 4-ring and 5-ring polycyclic aromatic hydrocarbons during ozonation and combined ozonation and biological treatment. The highest polycyclic aromatic hydrocarbon removal was obtained by combination of two-phase ozonation and bioremediation.